Optimization of Cranio-Orbital Remodeling. Issue 5 (July 2015) - Isaac, Kathryn V.; Koenemann, Jochen; Fukasawa, Ricardo; Qian, David; Linhares, Andre; Saber, Nikoo R.; Drake, James; Forrest, Christopher R.; Phillips, John H.; Nguyen, Phuong D.
<x xml:space="preserve">Abstract</x> Abstract Cranio-orbital remodeling aims to correct the dysmorphic skull associated with craniosynostosis. Traditionally, the skull is reconstructed into a shape that is subjectively normal according to the surgeon's perception. We present a novel technique using a mathematical algorithm to define the optimal location for bony osteotomies and to objectively reshape the fronto-orbital bar into an ideal normal skull contour. Using pre-operative computed tomography images, the abnormal skull contour at the frontal-orbital region was obtained for infants planned to undergo cranio-orbital remodeling. The ideal skull shape was derived from an age- and sex-matched normative skull library. For each patient, the mathematical technique of dynamic programming (DP) was applied to compare the abnormal and ideal skull shapes. The DP algorithm identifies the optimal location of osteotomy sites and calculates the objective difference in surface area remaining between the normative and dysmorphic skull shape for each solution applied. By selecting the optimal solution with minimal objective difference, the surgeon is guided to reproducibly recreate the normal skull contour with defined osteotomies. The DP algorithm was applied in 13 cases of cranio-orbital remodeling. Five female and 8 male infants with a mean age of 11 months were treated for craniosynostosis classified as metopic (n = 7), unicoronal (n = 4), or bicoronal (n = 2). The mean OR time was 190.2 min (SD 33.6), mean estimated blood loss 244 cc (SD 147.6), and 10 infants required blood transfusions. Compared with a historical crania-orbital remodeling group treated without application of the algorithm, there was no significant difference in OR time, estimated blood loss, or transfusion rate. This novel technique enables the craniofacial surgeon to objectively reshape the fronto-orbital bar and reproducibly reconstruct a skull shape resembling that of normal infants.